The Anti-Shibboleth: The Traumatic Character of the Shibboleth as Silence. (18th February 2020) - McNamara, Tim
Abstract: This article discusses the familiar notion of the shibboleth in situations of exclusion, focusing on the non-use, rather than the use, of language, for which I propose the term the anti-shibboleth. The article begins with an introduction to the concept of the shibboleth, giving examples from situations of violent conflict and suppression such as the Holocaust and the Cambodian genocide, and goes on to develop the notion of the anti-shibboleth, using further examples from such contexts. It then considers the situation of Aboriginal Australians in the period up until 1967 in the light of the concept. The article concludes with a discussion of the way in which we may understand the anti-shibboleth theoretically, drawing on insights from poststructuralism.